2003
DOI: 10.1111/j.1949-8594.2003.tb18123.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Professional Development, Teachers' Instructional Practices, and the Achievement of Students in Science and Mathematics

Abstract: The purpose of this study was to examine the relationship between different types of professional development, teachers' instructional practices, and the achievement of students in science and mathematics. The types of professional development studied included immersion, examining practice, curriculum implementation, curriculum development, and collaborative work. Data regarding teachers' instructional practices and the amount of professional development were collected using teacher surveys. Ninety‐four middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 13 publications
1
28
2
1
Order By: Relevance
“…A large body of research has shown that district and school PD efforts can result in changes in teachers' knowledge and beliefs as well as in their instructional practice (Loucks-Horsley and Matsumoto, 1999). Some researchers have even found direct effects on student achievement for some types of PD (Huffman, Thomas, and Lawrenz, 2003). In contrast, the lack of human capitalincluding insufficient staffing and limited staff commitment, knowledge, and skillscan hinder efforts to implement wide-scale reform (Burch and Spillane, 2004;Elmore and Burney, 1999;Massell and Goertz, 1999;Firestone, 1989;Spillane and Thomp-son, 1997).…”
Section: District and School Responses To Accountabilitymentioning
confidence: 99%
“…A large body of research has shown that district and school PD efforts can result in changes in teachers' knowledge and beliefs as well as in their instructional practice (Loucks-Horsley and Matsumoto, 1999). Some researchers have even found direct effects on student achievement for some types of PD (Huffman, Thomas, and Lawrenz, 2003). In contrast, the lack of human capitalincluding insufficient staffing and limited staff commitment, knowledge, and skillscan hinder efforts to implement wide-scale reform (Burch and Spillane, 2004;Elmore and Burney, 1999;Massell and Goertz, 1999;Firestone, 1989;Spillane and Thomp-son, 1997).…”
Section: District and School Responses To Accountabilitymentioning
confidence: 99%
“…Thus, there is a clear need for continuing professional development to promote ongoing teacher learning and improve teacher instructional practices [35,36]. The positive influence that teacher training or professional development programs have on teaching behavior has been well established in several school disciplines (e.g., science, mathematics) [37][38][39]. Despite the correlation between teacher training and improved teacher instructional practices, the literature is fraught with concern surrounding the current state of professional development in physical education (PE) [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…There seems to be an increased interest in coaching-a process whereby experienced teachers or teacher trainers provide instructional support, professional development opportunities, feedback and ideas about the design of teaching materials to classroom teachers-as a means to improve instruction and build the capacity of school staff members (Poglinco & Bach, 2004). Teachers and principals seem to believe that this will lead to improved student performance and achievement, as has been shown in research elsewhere (DfEE, 2001a, b, c;Huffman et al, 2003;Diaz-Maggioli, 2004).…”
Section: Introductionmentioning
confidence: 78%